(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Relevance of the work is to study the influence of quercetin and lipoate in treatment of experimental diabetes. Purpose. To study the membrane — protective impact of quercetin and lipoate on the retina and in particular on the lysosomes of the pigment epithelium in streptezotocin diabetes. Methods. Studies were conducted on white rats of the Wistar line weighing 180— 220 g. Two groups of animals with developing diabetes received oral lipoic acid and quercetin. Activity of lysosomal enzyme of the retina was determined using spectrophotometric assay methods. Results. Application of the lipoic acid and quercetin has a pronounced effect on membrane-stabilizing effect on the retina at different periods of development of the diabetic process. Both studied drugs not only increased the stability of the intracel-lular membranes but also greatly prevented lysosomal degradation of the retinal structures. Conclusions. The use of the lipoic acid and quercetin in development of experimental diabetes has the distinct stabilizing effect on the lysosomal membrane of the retina at different periods of the disease. The drugs under study largely inhibit the degradation of subcellular structures of the retina, which is a manifestation of some kind of the protective effect on the ultrastructural components of the visual analyzer in diabetes.